Mistyczne implikacje doktryny o miłości Aelreda z Rievaulx - Groń, Ryszard (Vox Patrum, 2010)
Bernard of Clairvaux, ordering the young Aelred to write a treatise on charity, recognized that he was no ordinary theologian. The work of De speculo caritatis confirmed this belief and demonstrated theological competencies of the Abbot of Rievaulx which placed him among the constructors of the Cistercian school of charity. His insightful analyses attest to his in-depth familiarity with the progress of God’s love penetrating the human heart. It certainly goes beyond the knowledge derived from the Augustinian theology, propagated in the monasteries at that time, traces of which are visible throughout his work. It is also the effect of his formative training with the novice monks during his years of being the Novice Master. Possibly, it is also influenced by his very own experience of God, reaching the levels of mystical closeness to God. All these components, void of the structure of the work subjected to the purpose outlined by St. Bernard, yielded quite a coherent doctrine on charity, from which logically follow mystical implications, i.e. the experience of God Himself. There is a summary and a few conclusions from these contemplations. 1. Alread does not explicitly talk about the human condition of viatoris much emphasized by contemporary theology, but he understands the man’s feeling of being lost without God and it is in Him that the Abbot sees completeness of human existence. Following the Augustinian conviction, he implies that nothing and nobody can give the man absolute happiness, except for God; this is why he will not cease seeking in his heart, his deepest actions of his spiritual powers, until he rests in God’s essence, truth and goodness. This is what the Abbot calls the eternal sabbath of God, which by itself is the internal life of the Holy Trinity, yet on the outside, it appears as the purpose of perfection for all creation. The man, naturally, has this divine sabbath etched deeply in his heart, since this is the disposition he received from his Creator, being made of His image (having spiritual faculties of God) and likeness (operations of these faculties drawing to God). 2. Love is the rule according to which the world exists and operates, and the man has an important role to play in it, due to his memory, conscience and freedom, whose operations liken him to God. Thanks to them, he can not only decipher the loving intentions of the Creator, but respond to them in a loving collaboration, which leads him to a happy union with God. This collaboration could not have been shattered even by the sin, redeemed through Christ’s blood, which became the beginning of a new loving proposition made by God and now available in the sacrament of faith and practice of caritas. Certainly, on the part of the man, this collaboration is now more difficult, since the sin weakened his spiritual powers, which in their forgetfulness, error and foolishness lean toward the objects of this world through physical desire. Human love, willing to return to its original form of collaboration with God, must now be ascetic in its character, expressed as mortifications, denials and sacrifices. Aelred calls it, „circumcision of the inner and the outer man”. 3. The circumcision stands for the internal work that the man must do to root the vices out of his heart and install virtues in their place. It is a slow process of spiritual comeback to God, which lasts throughout the entire life of a man and culminates in the eternal sabbath of God. At the same time, it is the time of receiving graceful love, continually supported and animated by God. It is a process of spiritual internalization, i.e. further and further departure from the exterior and physical objects so as to concentrate more and more on the internal and spiritual object of God’s presence in the deepest layers of the human heart, where the full union with God takes place. This union begins with the sacrament of faith received at baptism. Aelred only briefly mentions the mystery of God inhabiting (taking residence in) the human soul, which takes part with God’s grace poured out by the Holy Spirit, but he concentrates more on the idea of the sabbath, the rest, which makes possible participation in the life of God. 4. Aelred and the whole Cistercian school knew that the process of internalizing proceeds according to human nature; this is why he first mentions the basic grace of the humanity of Jesus Christ. The idea was to provide the man, through Jesus Christ, with physical and pious stimuli to make him fall in love with God’s charity and engage his feelings and senses so as to free him of his physical desires and direct his will toward the spiritual love. It is done through the practice of meditating the humanity, contemplating the Scriptures, especially the events from the life of Jesus Christ and his followers. Later on, special types of grace start to appear: compunction (compunctio), or the so called, God’s visits (spiritalis uisitationes), which depending on the stage of spiritual advancement in a man are designed to either awaken those who are asleep, i.e. numb, or console those who are saddened on their way, and lastly, to reward and sustain those who yearn for heavenly goods. Actually, Aelred distinguishes three moments within the long process of God’s intervention into the human soul, reflected in three stages of spiritual life: fear of the beginners, purification of the advanced and love of the accomplished. 5. This is where we can see most of the mystical repercussions of his teaching on charity. The initial visits make room for the next ones, and once their mission of inciting to greater love is complete they face the various trials and undertake, in the name of God, a number of mortifications, followed by practice of virtues. These, in turn, lead to even greater love. For example, the Abbot describes pouring of God’s grace into the human soul through basting in the glory and wisdom of God, so that the soul is lost in love and desires to become united with God in eternity. These are but special graces of God affecting human feelings; however they are not the unity with God, although they appear to be its powerful manifestations. It is only through engaging the will, which combines the functions of the other spiritual powers, that the unity with God’s will is accomplished, signs of that is the willingness of the soul to undertake mortifications and sacrifices for God. Then, it is not a surprise that „the yoke of Christ is sweet and the burden is light”. 6. The union of soul with God is truly about aligning the will (love) of the man with will (love) of God Himself, i.e. being directed by His Spirit and allowing to be transformed by His Divine caritas. It is possible, because caritas, like any human love, weaves into the human psychological structure, marking three distinct stages: choice (predilection), growth (action and desire) and fruits (attaining the object). Within the right choice Aelred distinguishes three types of love: of God, neighbor and oneself, although all of them lead to God, as their source. The Abbot pictured this in the idea of three sabbaths, complementing at the same time the concept of the eternal sabbath. The decisive moment of love is its movement, its growth: actions and desires, which make the man constantly prone and open to God, to unite with Him (rest in Him) finally in the eternal sabbath. 7. Alread makes a longer stop here to discuss the role of affections (affectus, passiones), which influence the actions of will. Besides reason, they are the cause of love’s movement. Their role is indispensable, because they lend inciting sweetness to a mystical encounter with God and stimulate to greater love. By themselves, however, they can be deceitful, when they are not subjected to the will. This is why he proposes to move not through the affections, but according to them, so that they are guided by the will. This is especially true in the case of love of neighbor. The general rule then is that neighbors would rejoice together in God and that each one would rejoice God in each other. Against this background, the Abbot promotes the spiritual affects received from God, rational ones encouraging developing virtues, official ones inducing to love a person, natural ones telling to love one’s friends and foes. He also permits physical affects, attracting with their outer appearance, as long as they do not lead to a vice. 8. The growing love finds its outlet in the fruits, which constitute the third and last component of the internal structure of love operating within the man. It is about rejoicing in the object attained, resting for spiritual powers on an object, which one desired in one’s love. Aelred considers temporary and eternal fruits. The latter refers to the ultimate union with God in heaven, after death, which is the rest in the eternal sabbath of God. We can taste it here on earth to ease human frailty, through contemplation and the sweetness of special graces of God. The former, on the other hand, appreciates the role of others (parents, teachers, instructors, friends) in acquiring the true wisdom of life; we use all of them to sweeten our lives and delight our spirit. Particularly helpful here is a friend, if there is one, who through spiritual friendship can share in our joys and sorrows, as well as the most intimate desires of the soul, so that they merge into unity in spirit. Two years ago, during the Cistercian Studies Conference at the 43rd International Medieval Studies Congress in Kalamazoo, Mi, a discussion was started as to the mystical competencies of Aelred of Rievaulx and his possible mystical predispositions. Our contemplations can cast some more light on this issue.